Understanding Generation Y : an investigation of how Hilton College can use technology for communication - Wyngaard, Richard Clive (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
Background to the academic research. Hilton College is an all boys private school in the Kwa-Zulu Natal Midlands. Since the beginning of 2012 boys have been permitted to carry their phones during the school day, (Thomson, 2012). Wireless internet access was also extended across the campus to allow boys and staff to bring their own devices to class and have access to the internet (Machlachlan, 2012). In the past, communication between staff and boys was either verbal or through the use of a daily notice, called the Daily Routine Order (DRO). The DRO is placed at the dining room tables each day and boys are expected to check for any notices that may pertain to them. These notices are emailed to a secretary who prints them out and places them in the dining room each day at lunch. 2. Objectives to the research. This research sought to establish whether current communication methods were effective or whether the prevalence of mobile phones and wireless devices had presented the school with a more effective method. It was important therefore, to investigate what devices were on campus, how those devices were used and when they were used. In addition to this, the research sought to establish communication preference among staff and boys. 3. Research Methodology. The research was conducted through the use of a qualitative survey that was conducted among both staff and boys. Staff and boys were surveyed to establish generation, device prevalence, device usage and device preference. This data was collected using an anonymous qualitative survey that was administered through the use of Google docs in the school labs. 187 Boys in 3 grades 8 and 9 participated in the survey along with 18 staff members. The data was then analysed and compared to data from similar research that had been conducted elsewhere in the world. Because of significant age differences between boys and staff it was critical to establish whether device usage among staff and boys was tied to their generation. Of particular interest were the device behaviours associated with the Millennial generation, who were born between 1982-2002 (Strauss 2005:10). This generational 'benchmark' allowed the researcher to compare the Hilton College cohort to those whose device behaviours and usage had occurred and been discussed in generational research elsewhere. It also allowed for certain assumptions to be made about staff and boys based on their generational profile. 4. Findings It was found that staff and boys exhibited communication traits that were consistent with their generation and consistent with other research in this field. It was also found that staff and boys preferred mobile and digital forms of communication over verbal announcements and the DRO system. For this reason, it was recommended that the Hilton College establish a system that took advantage of technology to improve on communication. Various recommendations were given by the researcher that took advantage of current technologies. These included the use of SMS, Instant Messaging, Social Networks and email. It was also recommended that the school consider prescribing devices that allow for communication between staff and boys.
Keywords: Generation Y -- South Africa -- KwaZulu-Natal; Cell phones -- Social aspects; Mobile communication systems -- Social aspects; Information technology -- South Africa -- KwaZulu-Natal